Flooding Alters Plant‐Mediated Carbon Cycling Independently of Elevated Atmospheric CO2 Concentrations. Issue 6 (29th June 2018) - Jones, Scott F.; Stagg, Camille L.; Krauss, Ken W.; Hester, Mark W.
Abstract: Plant‐mediated processes determine carbon (C) cycling and storage in many ecosystems; how plant‐associated processes may be altered by climate‐induced changes in environmental drivers is therefore an essential question for understanding global C cycling. In this study, we hypothesize that environmental alterations associated with near‐term climate change can exert strong control on plant‐associated ecosystem C cycling and that investigations along an extended hydrologic gradient may give mechanistic insight into C cycling. We utilize a mesocosm approach to investigate the response of plant, soil, and gaseous C cycling to changing hydrologic regimes and elevated atmospheric carbon dioxide (CO2 ) concentrations expected by 2100 in a coastal salt marsh in Louisiana, USA. Although elevated CO2 had no significant effects on C cycling, we demonstrate that greater average flooding depth stimulated C exchange, with higher rates of labile C decomposition, plant CO2 assimilation, and soil C respiration. Greater average flooding depth also significantly decreased the soil C pool and marginally increased the aboveground biomass C pool, leading to net losses in total C stocks. Further, flooding depths along an extended hydrologic gradient garnered insight into decomposition mechanisms that was not apparent from other data. In C‐4 dominated salt marshes, sea level rise will likely overwhelm effects of elevated CO2 with climate change. Deeper flooding associated with sea level rise may decrease long‐term soil C pools and quicken C exchange between soil and atmosphere, thereby threatening net C storage in salt marsh habitats. Manipulative studies will be indispensable for understanding biogeochemical cycling under future conditions. Plain Language Summary: This study examines how near‐term climate change may affect the exchange and storage of carbon by plants in salt marshes. Our results indicate that sea level rise will increase the amount of carbon that is moved from the soil into the atmosphere, shrinking the amount of carbon in salt marsh soil. This may reduce the ability of salt marshes to keep carbon in soil long term and decrease the ability of salt marshes to offset climate change. As salt marshes are some of the best ecosystems on the planet for storing carbon in soils, any change in how these ecosystems process carbon is important to understand. Key Points: We quantify changes in plant‐mediated carbon cycling to altered hydrology and CO2 concentrations in a blue carbon salt marsh system Greater average flooding depth increased plant carbon exchange and decreased the total carbon pool The drivers of cellulose decomposition were not constant over an extended hydrologic gradient